2018
DOI: 10.1007/s11356-018-2294-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of biomonitoring methods applying tropical bioindicator plants for assessing the phytoxicity of the air pollutants in SE, Brazil

Abstract: In the tropical region, the greatest challenge of the biomonitoring approach is to establish linear relationships between biomarkers measured in plants and pollutant concentrations, since the bioindicator responses can be intensified or restricted by climatic variations. In southeastern Brazil, there are two regions affected by air pollution, where the Atlantic Forest remains and should be preserved. Consequently, both areas have been monitored by biomonitoring procedures using standardized and tropical plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 99 publications
0
9
0
3
Order By: Relevance
“…Greening plants may serve as a cost effective and environmentally compatible means for the biomonitoring of pollutants in urban settings, as plant materials (e.g., tree leaves and bark) are easy to collect, may be analyzed cheaply, and produce no secondary pollution [22,23]. Thus, plants can be widely utilized for the removal of airborne contaminants in urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…Greening plants may serve as a cost effective and environmentally compatible means for the biomonitoring of pollutants in urban settings, as plant materials (e.g., tree leaves and bark) are easy to collect, may be analyzed cheaply, and produce no secondary pollution [22,23]. Thus, plants can be widely utilized for the removal of airborne contaminants in urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2016) have shown that plants are considered as the effective and the best system for biomonitoring and acting as bioindicators for atmospheric pollutants especially for heavy metals. Biomonitoring by plant species has been carried out in two ways as passive monitoring and active monitoring techniques, first one is by planting or introducing the sensitive plants and the later one is using the plants existing at present in the environment (Nakazato et al, 2018). Polluted sites specifically with various metal pollutants were monitored frequently by the lower plants such as mosses and lichens due to their more accumulation ability (Jiang et al, 2018 andYatawara andDayananda 2019).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2013 Avaliar a troca do combustível utilizado nas caldeiras de uma refinaria de petróleo bruto. (Nakazato et al, 2018). Portanto, a escolha da espécie P.guajava no presente trabalho se deu pela facilidade de obtenção das mudas e pela versatilidade do uso na investigação de poluentes no ambiente.…”
Section: Análises De Hpas E Mpunclassified
“…As concentrações de B foram de 38,1 ppm (C2), 37,5 ppm (C3), 40,6 ppm (C4) e 41,6 (P1). Este elemento é também descrito como proveniente de fontes naturais, principalmente marinhas, que proporcionalmente, contribuem com uma maior parte nas emissões de B para a atmosfera (Howe, 1998 apresentaou um valor médio de 32,7 ppm de B (Nakazato et. al.…”
Section: Análise De Metais  Digestão De Amostrasunclassified
See 1 more Smart Citation